Human Rights and People's Sovereignty from the Perspective of Article 28 Chapter XA of the 1945 Constitution: A Case Study of the Struggle for Jobs by Foreign Workers - Astuti, Sri Ayu (Jurnal Hukum dan Keadilan, 2025)
The phenomenon of the increasing use of foreign workers (TKA) in Indonesia has given rise to debate regarding the protection of citizens' rights to work as guaranteed in Article 28D paragraph (2) of the 1945 Constitution. On the one hand, government policies oriented towards increasing foreign investment are considered important for national economic development, but on the other hand, they give rise to the potential for violations of the principles of Human Rights (HAM) and People's Sovereignty as regulated in Article 28 Chapter XA of the 1945 Constitution. This study aims to analyze the application of the principles of human rights and people's sovereignty in the context of the struggle for employment between local and foreign workers, and to assess the state's constitutional responsibility in protecting the right to work. The method used is qualitative with a case study approach through interviews, observations, and legal document reviews. The results of the study indicate that the implementation of the right to work in the context of the use of TKA does not fully reflect the principle of people's sovereignty, because the government emphasizes the economic aspect more than protecting the rights of local workers. As a result, inequality in access to work and a decline in public trust in the state has emerged. This study emphasizes the importance of reorienting employment policies to align with human rights values ​​and the principle of people's sovereignty.